2019
DOI: 10.1002/ecm.1351
|View full text |Cite
|
Sign up to set email alerts
|

Eighteen years of ecological monitoring reveals multiple lines of evidence for tundra vegetation change

Abstract: The Arctic tundra is warming rapidly, yet the exact mechanisms linking warming and observed ecological changes are often unclear. Understanding mechanisms of change requires long‐term monitoring of multiple ecological parameters. Here, we present the findings of a collaboration between government scientists, local people, park rangers, and academic researchers that provide insights into changes in plant composition, phenology, and growth over 18 yr on Qikiqtaruk‐Herschel Island, Canada. Qikiqtaruk is an import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
145
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(154 citation statements)
references
References 131 publications
(380 reference statements)
9
145
0
Order By: Relevance
“…Consistent with these field observations, our results show that Qikiqtaruk‐Herschel Island experienced an increase in shrub cover of 9.67 km 2 (+59.5% relative to 1984) and reductions in sparse vegetation and barren land of 4.69 km 2 (−36.6% relative to 1984). These changes coincide with a 2.5–4°C increase in air temperature, earlier snow melt, and decreased frost frequency over the island (Myers‐Smith et al, ), suggesting that climate warming is the key driver behind shrub expansion. The spatial pattern of shrub expansion appears to follow the patterns of rivers or other hydrological channel, suggesting a role of changing hydrology in the proliferation of Arctic shrubs.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Consistent with these field observations, our results show that Qikiqtaruk‐Herschel Island experienced an increase in shrub cover of 9.67 km 2 (+59.5% relative to 1984) and reductions in sparse vegetation and barren land of 4.69 km 2 (−36.6% relative to 1984). These changes coincide with a 2.5–4°C increase in air temperature, earlier snow melt, and decreased frost frequency over the island (Myers‐Smith et al, ), suggesting that climate warming is the key driver behind shrub expansion. The spatial pattern of shrub expansion appears to follow the patterns of rivers or other hydrological channel, suggesting a role of changing hydrology in the proliferation of Arctic shrubs.…”
Section: Resultsmentioning
confidence: 82%
“…However, the shrub expansion we map here is borne out by in situ observations. For example, Figure shows land cover changes that we map on Qikiqtaruk‐Herschel Island, Yukon Territory, a small (136 km 2 ) island off the northern coast of Canada, along with a pair of photos collected across a 27 year time span (1987 and 2014) on the island (Myers‐Smith et al, ). These photos confirm pronounced increases in the height and cover of Salix richardsonii shrubs in locations that were previously dominated by herbaceous vegetation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coastal erosion mobilises large amounts of sediment, organic matter, and nutrients from permafrost Overduin et al, 2014;Retamal et al, 2008;Wegner et al, 2015), which are released into the nearshore waters and affect marine ecosystems (Bell et al, 2016;Dunton et al, 2006;Fritz et al, 2017). Several studies have reported signs of accelerating coastal erosion rates at locations around the Arctic, including the western Arctic (Barnhart et al, 2014;Jones et al, 2008Jones et al, , 2009bMars and Houseknecht, 2007;Radosavljevic et al, 2016) and Siberia Kritsuk et al, 2014;Novikova et al, 2018;Ogorodov et al, 2016). However, the spatiotemporal resolution of circum-Arctic studies limits inferences of widespread changes in coastal erosion rates (Fritz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The use of remote sensing to measure changes in permafrost landscapes is increasingly common (Novikova et al, 2018). However, optical image coverage in high-latitude regions has historically been widely limited to relatively coarse temporal and spatial resolutions, due to frequent cloud cover and logistical challenges that limit both satellite observations and aerial surveys .…”
Section: Introductionmentioning
confidence: 99%